2018
DOI: 10.1097/md.0000000000013432
|View full text |Cite
|
Sign up to set email alerts
|

Dark chocolate modulates platelet function with a mechanism mediated by flavan-3-ol metabolites

Abstract: Cocoa is a rich source bioactive compounds, i.e., flavan-3-ols, and its consumption has been associated with several beneficial effects, such as the positive modulation of the hemostasis targeted by the platelet function. However, these phenolic compounds have a very low bioavailability and extensively undergo phase I and II metabolism, with the appearing into the bloodstream of (epi)catechin conjugates and phenyl-γ-valerolactones and their conjugates, at different times.The aims of this study were to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…Neither un-metabolized epicatechin and catechin nor procyanidins B1 and B2 were detected in the collected biological fluids in agreement with previous studies [4,11,16,22,23,24,25]. Only Schroeter et al [26] described the presence of epicatechin and catechin in plasma after the ingestion of powdered cocoa drinks with a high flavanol content (917 mg).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Neither un-metabolized epicatechin and catechin nor procyanidins B1 and B2 were detected in the collected biological fluids in agreement with previous studies [4,11,16,22,23,24,25]. Only Schroeter et al [26] described the presence of epicatechin and catechin in plasma after the ingestion of powdered cocoa drinks with a high flavanol content (917 mg).…”
Section: Discussionsupporting
confidence: 88%
“…However, other studies have shown a correlation between the effect of dark chocolate (50 g, providing 7.5 gallic acid equivalents (GAE) of polyphenols) improving platelet function and the increased plasma concentrations of structurally-related (epi)catechin metabolites (SREM). These data confirm that the potential health benefits of cocoa consumption may be mediated by flavan-3-ol circulating metabolites [11], in spite of the limited bioavailability of cocoa polyphenols.…”
Section: Introductionsupporting
confidence: 78%
“…Therefore, these various metabolites reach their plasma peak nearly 2 h following oral intake [ 27 , 49 ]. Several sulfates, glucuronide, and methyl metabolites of epicatechin have been identified in the plasma and urine after ingestion of 100 g of dark chocolate [ 55 ].…”
Section: Cocoa Polyphenols Metabolism and Bioavailabilitymentioning
confidence: 99%
“…Phenolic metabolites were then extracted and concentrated using a solid phase extraction (SPE) method previously reported [33] and were analysed by a UHPLC DIONEX Ultimate 3000 equipped with a triple quadrupole TSQ mass spectrometer (Thermo Fisher Scientific Inc., San José, CA, USA) fitted with a heated-ESI (H-ESI) (Thermo Fisher Scientific Inc., San José, CA, USA) probe. Chromatographic separation, ionisation parameters, and spectrometric characteristics of the considered compounds were set as previously reported [34,35]. Quantification was performed with calibration curves of standards, when available or using the most structurally similar compound [34,35].…”
Section: Biological Samples Analysismentioning
confidence: 99%
“…Chromatographic separation, ionisation parameters, and spectrometric characteristics of the considered compounds were set as previously reported [34,35]. Quantification was performed with calibration curves of standards, when available or using the most structurally similar compound [34,35]. Data processing was performed using Xcalibur software (Thermo Scientific Inc., Waltham, MA, USA).…”
Section: Biological Samples Analysismentioning
confidence: 99%